PENGARUH BERMAIN PUZZLE BERBASIS ICT TERHADAP MOTIVASI BELAJAR DAN KEMAMPUAN MEMBACA PERMULAAN ANAK USIA 5-6 TAHUN - Nurlilawaty Nurlilawaty; Sri Milfayetti; Anita Yus (JURNAL TEMATIK, 2018)
This study aims to find out: (1) Differences in the ability to read the beginning of words and images of children aged 5-6 years through ICT-based puzzle play with conventional puzzle playing at TK Salsabila Al-Fazira; (2) Differences in Motivation Learning children who play ICT-based puzzles with children who play Conventional Puzzles at TK Salsabila Al-Fazira; This research is a quasi-experimental study. The results showed that: (1) Average Ability to read the beginning of the beginning of words and images of students who received ICT-based puzzle learning by 21.32 was greater than students who received conventional Puzzle learning at 15.04; (2) Motivation for learning that is taught using ICT-based D puzzles and students taught using conventional puzzles. Learning motivation of students who get ICT-based puzzle learning of 17.44 is greater than students who get conventional puzzle learning at 14.88. Learning with ICT-Based Puzzles is one alternative for teachers in presenting subject matter, it can be seen that the Application of ICT-Based Puzzle Learning can improve the ability to read the beginning of words and images, and student learning motivation